Plasmon polaritons in photonic superlattices containing a left-handed material (2009)
ABSTRACT: We analyze one-dimensional photonic superlattices which alternate layers of air and a left-handed material. We assume Drude-type dispersive responses for the dielectric permittivity and magnetic permeability of the left-handed material. Maxwell’s equations and the transfermatrix technique are used to derive the dispersion relation and transmission spectra for the propagation of obliquely incident optical fields. The photonic dispersion indicates that the growth direction component of the electric (or magnetic) field leads to the propagation of electric (or magnetic) plasmon polaritons, for either TE or TM configurations. Furthermore, we show that if the plasma frequency is chosen within the photonic (n(ω)) =0 zeroth-order bandgap, the coupling of light with plasmons weakens considerably. As light propagation is forbidden in that particular frequency region, the plasmon-polariton mode reduces to a pure plasmon mode